Geostatistical Model Development and Assessment of Tidal Stream Energy Resources: A Case Study of Indus Delta, Pakistan - Mirza Salman Baig; Insaf, Ambreen; Javaid, Saba; Uddin, Zaheer (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2024)
In this paper, an approach is applied by using the Geographical Information System for the development of geostatistical models to assess available tidal stream energy resources of the Indus Delta Creek system. The mean spring tidal current of twelve different locations in the Indus Delta Creek system (Pakistan) is utilized to develop geostatistical models for the prediction of tidal currents at different locations where no data was available. Models are validated and an investigation of prediction error is carried out to select the best model. For the prediction of tidal stream data, various models are collated namely (i) Circular (ii) K-Bessel (iii) Stable, and (iv) Exponential. These models show the range of mean spring ebb current between 1.9 m/s and 2.12 m/s and the range of mean spring flood current between 1.4 m/s and 1.65 m/s. The stable model for mean spring flood current and circular model for mean spring ebb current agreed with the observed ones. Furthermore, the tidal kinetic power density model and bathymetry model are also developed for the selection of potential sites within the study area. Based on results achieved from geostatistical and bathymetry models; deployment of the suitable turbine at the study area is proposed and generation of 2754.7 MW electric power is estimated.